2006
DOI: 10.1002/jcc.20497
|View full text |Cite
|
Sign up to set email alerts
|

Transition metal–boron complexes BnM: From bowls (n = 8–14) to tires (n = 14)

Abstract: Transition metal-boron complexes BnM have been predicted at density functional theory level to be molecular bowls (n = 8-14) hosting a transition metal atom (M) inside or molecular tires (n = 14) centered with a transition metal atom. Small Bn clusters prove to be effective inorganic ligands to all the VB-VIIIB transition metal elements in the periodic table. Density functional evidences obtained in this work strongly suggest that bowl-shaped fullerene analogues of Bn units exist in small BnM complexes and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Si@B 8 [5] , Ge@B 9 + , and Sn@B 10 2+ [6] represented typical theoretical speculations of planar hyper-coordinate group 14 elements in boron rings. We recently investigated the possibility of the sandwich-typed [η 6 -B 6 X] 2 M (X=C, N; M=Mn, Fe, Co, Ni) [7] and bowl-and tire-shaped B n M [8] at density functional theory (DFT) level. We also presented a universal structural pattern for planar hyper-coordinate Si in B n H 2 Si series [9] .…”
Section: Introductionmentioning
confidence: 99%
“…Si@B 8 [5] , Ge@B 9 + , and Sn@B 10 2+ [6] represented typical theoretical speculations of planar hyper-coordinate group 14 elements in boron rings. We recently investigated the possibility of the sandwich-typed [η 6 -B 6 X] 2 M (X=C, N; M=Mn, Fe, Co, Ni) [7] and bowl-and tire-shaped B n M [8] at density functional theory (DFT) level. We also presented a universal structural pattern for planar hyper-coordinate Si in B n H 2 Si series [9] .…”
Section: Introductionmentioning
confidence: 99%
“…Some studies done by the Li's group showed that boron clusters could be used to design sandwich structures with transition metal atoms: in the first instance, Li et al showed that the planar B 6 clusters with carbon or nitrogen atoms at the center demonstrate the capability in coordinating transition metal atoms to form sandwich complexes. 21 It is important to note that Boldyrey and Wang et al reported a combined photoelectron spectroscopy and ab initio study on MB 12 − (M = Co, and Rh) clusters. 21 It is important to note that Boldyrey and Wang et al reported a combined photoelectron spectroscopy and ab initio study on MB 12 − (M = Co, and Rh) clusters.…”
Section: Introductionmentioning
confidence: 99%
“…60 Chemical bonding analysis reveals that delocalized multicenter-two-electron (nc-2e) σ and π bonds in all boron system stabilize the clusters, which makes the formation of metal-doped boron cluster available. 56 The boron-ligand metal compounds of wheel-type 61-65 and bowl-shape 66,67 have been reported. Cheng and Yuan 68 state the ferrocene-like sandwich complexes Cr (B 12 ) 2 , and the spdπ interaction between Cr and boron ligand is investigated.…”
Section: Introductionmentioning
confidence: 99%